Factors affecting course satisfaction of online Malaysian university students - Khalid, Nasir M., author; Timpson, William M., advisor; Quick, Don, advisor; Kaminski, Karen, committee member; Unnithan, N Prabha, committee member (Colorado State University. Libraries, 2014)
Course satisfaction in online learning has grown into a concern among online educators, in order to prevent students from dropping, withdrawing, or otherwise leaving their course of study online. Researchers have established three main factors that have an influence on online students' course satisfaction: social, teaching, and cognitive presence. Adapting the Community of Inquiry (CoI) model, this study investigated the association between these presences and other possibly related factors, and their influence on students' course satisfaction with online courses just completed at a University in Malaysia. Concurrently, it also attempted to weigh these constructs and variables according to their impact on course satisfaction. Results show that all presences and age were significantly associated with course satisfaction. Also, course satisfaction was found to differ by gender, undergraduate and postgraduate students but was not by core and elective courses. Teaching presence, social presence, and age were found to be significant predictors of course satisfaction when statistically analyzed by a series of two-step hierarchical linear regressions.
Keywords: cognitive presence; course satisfaction; learning management system; online/hybrid learning; social presence; teaching presence